Exploring the Relationship Between Smartphone Addiction, Attention Difficulties, and Occupational Accident Risk Among Health Science Interns: A Cross-Sectional Study. - Kiliç, Mahmut; Uslukiliç, Güllü; Melez, Yeşim; Türksoy, Vugar A. (Indian Journal of Occupational & Environmental Medicine)
Background: The widespread use of smartphones among healthcare students raises concerns about cognitive and occupational safety impacts. This study aimed to examine the relationships between smartphone addiction, attention difficulties, and susceptibility to occupational accidents among university students in health science internships. Methods: A cross-sectional study was conducted in 2023 with 553 volunteer university students enrolled in the health sciences programs at Yozgat Bozok University Hospital. Participants were selected using a convenience sampling method. The study site was a university hospital in central Türkiye, where students were completing clinical internships. Data were collected using validated scales, and the analysis plan included descriptive statistics, Pearson correlation, and multivariate linear regression to examine associations between variables. Results: Significant positive correlations were found between smartphone addiction and attention difficulties (r = 0.510), accident susceptibility (r = 0.504), and daily smartphone use (r = 0.314). Regression analysis showed that attention difficulties were primarily influenced by smartphone addiction. Susceptibility to accidents was mainly predicted by attention difficulties, smartphone addiction, and being a student in nursing, midwifery, or medicine (Adj. R ² =0.473). Occupational accident risk was associated with susceptibility to accidents, higher risk perception, off-campus work, lack of occupational health and safety training, attention difficulties, nursing education, and previous accident experience (Adj. R ² =0.238). Conclusion: The study found that smartphone addiction is significantly associated with increased attention difficulties, which in turn elevate students' susceptibility to occupational accidents. Smartphone use may thus indirectly increase accident risk in clinical settings.